Identifying typologies of synthetic energy justice: Eco-centric and anthropocentric perspectives - Seo, Inseok; Lee, Youhyun (Energy and Environment, 2024)
Since the concept of energy justice emerged, studies have conceptually, but rarely empirically, explored energy justice. In addition, studies on energy justice have mainly focused on anthropocentric values toward energy justice. This study aims to categorize Organization for Economic Cooperation and Development (OECD) countries’ energy justice using synthetic energy justice via two aspects: eco-centrism and anthropocentrism. Each aspect of energy justice is sub-divided into distributive, substantive, and procedural justices. Using a fuzzy set qualitative comparative analysis methodology via a statistical program, we suggest typologies of 35 OECD countries for each aspect. Eight types of energy justice for each aspect are extracted, and four types of synthetic energy justice groups are identified among OECD countries. Austria, Iceland, and Luxembourg show the best performance in synthetic energy justice, but do not reach a complete contestable status from an eco-centric perspective. This study provides practical policy implications for OECD countries to self-evaluate each country's macroscopic policy direction in the energy sector, and to ultimately pursue synthetic energy justice with a balanced perspective for our environment and us.
Keywords: Anthropocentrism; Development countries; Eco-centrism; Energy justices; Fuzzy ideal type analyse; Fuzzy ideals; Ideal types; Organization for economic co-operation and development; Synthetic energy justice; Type analysis; anthropocentrism; eco-centrism; Fuzzy ideal type analysis; synthetic energy justice